Molybdenum‐isotope chemostratigraphy and paleoceanography of the Toarcian Oceanic Anoxic Event (Early Jurassic). (10th August 2017) - Dickson, Alexander J.; Gill, Benjamin C.; Ruhl, Micha; Jenkyns, Hugh C.; Porcelli, Donald; Idiz, Erdem; Lyons, Timothy W.; van den Boorn, Sander H. J. M.
Abstract: Molybdenum (Mo)‐isotope chemostratigraphy of organic‐rich mudrocks has been a valuable tool for testing the hypothesis that the Toarcian Oceanic Anoxic Event (T‐OAE, Early Jurassic, 183 Ma) was characterized by the spread of marine euxinia (and organic matter burial) at a global scale. However, the interpretation of existing Mo‐isotope data for the T‐OAE (from Yorkshire, Cleveland Basin, U.K.) is equivocal. In this study, three new Mo‐isotope profiles are presented: from Dotternhausen Quarry (South German Basin, Germany), the Rijswijk core (West Netherlands Basin, Netherlands), and the Dogna core (Belluno Basin, northern Italy). Precise biostratigraphic and chemostratigraphic correlation between the three sites allows a direct comparison of the data, enabling some key conclusions to be reached: (i) The Mo‐isotope composition of seawater during the peak of the T‐OAE was probably close to 1.45‰, implicating a greater removal flux of sulphides from seawater, and a larger extent of global seafloor euxinia compared to the present day; (ii) Mo‐isotope cycles previously identified in the Yorkshire sedimentary succession are attributed to changes in the degree of local Mo drawdown from overlying Cleveland Basin seawater; (iii) The consistency of the new multisite Mo‐isotope data set indicates a secular reduction in the burial of Mo globally in the late stages of the T‐OAE, implying a contraction in the extent of global marine euxinia; (iv) Subtle differences in the Mo‐isotope composition of deposits formed in different euxinic subbasins of the European epicontinental shelf were probably governed by local variations in basin hydrography and rates of water renewal. Key Points: The global seawater Mo‐isotope composition during the early stages of the T‐OAE was constant Sedimentary Mo‐isotope fluctuations in Yorkshire during the early stages of the T‐OAE record local hydrographic phenomena Stratigraphic changes in Mo‐isotope compositions suggest a secular decline in global anoxia following the T‐OAE